2014
DOI: 10.1136/bcr-2013-202515
|View full text |Cite
|
Sign up to set email alerts
|

Delayed onset panuveitis following intravitreal aflibercept injection

Abstract: Aflibercept has been listed on the Australian Pharmaceutical Benefit Scheme for the past year for neovascular age-related macular degeneration. Since that time there have not been any reports of delayed onset panuveitis. We present two cases of anterior and posterior uveitis that have occurred 4 weeks or more after first intravitreal injection of aflibercept. Both patients had received other vascular endothelial growth factor inhibitors prior to aflibercept administration without signs of inflammation and both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In one published report, 3 20 cases were identified from a single practice with similar characteristics and outcomes to those presented in this report. In another report, 4 2 cases of panuveitis arose more than 4 weeks after aflibercept injection.…”
Section: Discussionmentioning
confidence: 91%
“…In one published report, 3 20 cases were identified from a single practice with similar characteristics and outcomes to those presented in this report. In another report, 4 2 cases of panuveitis arose more than 4 weeks after aflibercept injection.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, bevacizumab showed a signif- Original article icant inverse association with both retinal haemorrhage and uveitis. An Australian case report on uveitis following the use of intravitreal aflibercept also cautions clinicians to be aware of late-onset sterile uveitis and vitritis after aflibercept injection [19]. Conversely, a double-blind randomised controlled trial showed that aflibercept was associated with similar visual and anatomic outcomes as ranibizumab when dosed monthly, as well as similar safety and tolerability [20].…”
Section: Discussionmentioning
confidence: 99%
“…Sterile inflammation following the intravitreal aflibercept injection is previously reported but its cause is still unknown [510]. The American Society of Retina Specialists' therapeutic surveillance subcommittee first reported 15 cases of aflibercept related sterile inflammation [6] and later expanded this series to 56 cases from the practices throughout the United States between December 2011 and February 2014 [10].…”
Section: Discussionmentioning
confidence: 99%